Czuj w czas o sobie cny czytelniku Pieśni V Jana Kochanowskiego - Bakuła, Kordian (Dydaktyka Polonistyczna, 2020)
The article concerns the school reading of the Songs V, Eternal Disgrace of J. Kochanowski,which has been present in high school’s and technical school’s textbooks for decades. The criticalmoment is not understanding certain expressions, such as a „pitiful loot”, „to manage light people”,„we get in”, which leads to a weakening of the understanding of the entire piece. The author drawsattention to the insufficient number of footnotes in the textbooks, not always correct, and thereforeproposes to increase the linguistic and factual explanations, improve the existing ones, for which heused historical and contemporary dictionaries. He calls for readers’ vigilance, especially importantin the case of old novels.